Social Construction of Papua’s Indigenous People (OAP) Regarding the Unitary State of the Republic of Indonesia - Ramazakir , Udin; Arifin , Syamsul; Nurjaman, Asep; Rustamadji, Rustamadji (Edujavare Publishing, 2026)
In the discourse on the modern nation-state, citizenship can no longer be understood merely as a formal and final legal status. The purpose of this study is to explore the construction of the meaning of the Unitary State of the Republic of Indonesia (NKRI) in the daily life experiences of indigenous Papuans (OAP), highlighting the ambivalence between the finality of state law and the subjective experiences of citizens. This research method uses a qualitative approach, applying phenomenological-hermeneutic methods. Data were collected through in-depth interviews, participant observation, and document analysis in various regions of Papua, including Jayapura City, Jayapura Regency, Keerom Regency, Manokwari Regency, Jayawijaya Regency, and Merauke Regency. The results show that the meaning of NKRI for indigenous Papuans is situational, historical, and relational. NKRI emerges paradoxically: as an administrative structure and national symbol that is followed procedurally, but often does not resonate affectively. The processes of externalization, objectivation, and internalization of the state give rise to conflicting meanings that are negotiated daily through social practices, symbols, and bodily experiences. This ambivalence influences the experience of citizenship, signaling the state's emotionally fragile legitimacy despite its legal validity. These findings emphasize that nationalism and citizenship are not final identities, but rather processes of meaning that are continually negotiated. This research contributes to academic understanding by broadening the understanding of citizenship as it manifests in postcolonial and conflict-ridden contexts, and by emphasizing the importance of recognizing citizens' subjective experiences in constructing state legitimacy.